89.7k views
1 vote

4(2x + 7) = 12 - 2(10 - 2x)
how do I solve this?​

1 Answer

5 votes

In this question, you're solving for x.

Solve for x:

4(2x + 7) = 12 - 2(10 - 2x)

Use the distributive property to distribute the 4 to the variables inside the parenthesis:

8x + 28 = 12 - 2 (10 - 2x)

You would also use the distributive property to distribute the -2 to the variables inside the parenthesis:

8x + 28 = 12 - 20 + 4x

Subtract 4x from both sides

4x + 28 = 12 - 20

4x + 28 = -8

Subtract 28 from both sides

4x = -36

Divide both sides by 4

x = -9

Answer:

x = -9

User Liquidity
by
5.2k points